2017
DOI: 10.1007/s10528-017-9832-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Stimulator of Interferon Genes (STING) Expression by Interferon-γ in Human Keratinocytes

Abstract: Infection of microbial pathogen triggers the innate immune system, and the induction of interferons (IFNs) play a vital role in host antiviral response. Stimulator of interferon genes (STING) was identified as a crucial regulator of the DNA sensing pathway, and activates both nuclear factor-κB and interferon regulatory factor 3 transcription pathways to evoke IFNs production. In this study, we studied the upregulation of STING mRNA expression, induced by IFN-γ in human keratinocytes (HaCaT). STING promoter ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In keratinocytes, IFN‐γ but not IFN‐β, TGF‐β or TNFα was found to up‐regulate STING expression. Phosphorylated STAT1 dimers downstream of IFN‐γ sensing can bind and activate the STING promoter . In macrophages, on the other hand, type I IFN can induce STING expression, through STAT1/STAT2/p48 binding to a different region of the promoter .…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In keratinocytes, IFN‐γ but not IFN‐β, TGF‐β or TNFα was found to up‐regulate STING expression. Phosphorylated STAT1 dimers downstream of IFN‐γ sensing can bind and activate the STING promoter . In macrophages, on the other hand, type I IFN can induce STING expression, through STAT1/STAT2/p48 binding to a different region of the promoter .…”
Section: Basic Biology Of the Sting Pathwaymentioning
confidence: 99%
“…Phosphorylated STAT1 dimers downstream of IFN-γ sensing can bind and activate the STING promoter. 50 In macrophages, on the other hand, type I IFN can induce STING expression, through STAT1/STAT2/p48 binding to a different region of the promoter. 51 KDM5 family demethylases carry out additional regulation at the STING promoter by removing H3K4 trimethylation and limiting transcription.…”
Section: Mechanistic Insights Into Sting Function and Regulationmentioning
confidence: 99%
“…STING is a transmembrane protein found in mitochondria and endoplasmic reticulum that regulates IFN-promotor activation at the downstream of RIG-I [40]. Zhang et al studied the effect of USP18 (also known as UBP43) on STING and revealed that USP18 interacts with STING to affect IFN-promotor activity [41].…”
Section: Usp18 and Usp20mentioning
confidence: 99%
“…We next examined the STING promoter sequence (−803 to +139) between 293 and 293T cells and found that their sequences were identical to one another and to published sequences [22,23]. Since there were no mutations between the promoter sequences, we hypothesized that SV40 large T antigen might be inhibiting STING promoter activity.…”
Section: Lack Of Sting Expression In 293t Cells Traces To a Defect Inmentioning
confidence: 99%